Match performance in a reference futsal team during an international tournament - implications for talent development in soccer - Yiannaki, C.; Barron, D. J.; Collins, D.; Carling, C. (Biology of Sport, 2020)
Anecdotal evidence suggests that futsal can aid talent development for 11 a-side soccer through the potential for transfer of the game`s skills and constraints. However, additional scientific research is necessary to enhance understanding of the technical and physical demands of futsal and the potential returns for soccer player development. Accordingly, this study examined selected characteristics of physical (internal and external loads) and technical performance in international futsal match-play in order to study the potential of these for skill transfer and aiding soccer player development. Performance was investigated in futsal players (n = 16, 25.74±4.71 years) belonging to a national team during an international tournament. Pre-tournament fitness testing determined maximum heart rate (MHR) via the Yo-Yo IR1 test (194.6±11.1 beats min-1) to aid interpretation of internal load via heart rate measures during match-play. External load (accelerations and deceleration events) was measured using an inertial movement unit. Finally, post-tournament analysis of selected technical events was performed. Results reported a mean heart rate value during `court time` of 164.7±22.3 beats min-1, which as a percentage of participants` MHR was 87.7%±4.4%, and a mean peak MHR of 98.3±2.5%. Results showed 2.16±0.25 accelerating (>1.5 m·s-2) and 2.78±0.13 decelerating (>1.5 m·s-2) events per player per minute. Team statistics included 647 passing, ~51 dribbling and 78 set play events per team per game. Match analyses showed that 77.3% of ball receptions were completed with the sole of the foot. Assessment of two-footedness showed 80.1±16.7% of individual possessions used the dominant foot to receive and 84.1±10.7% to pass the ball thereby displaying strong foot dominance. These results have quantified characteristics of elite futsal match-play that are no doubt intrinsically related to the environmental and task constraints of the sport. In addition to enhancing understanding of futsal, there are potential learning returns and implications for skills transfer and the development of soccer players.